The Influence of Service Quality and Brand Image on Mixue Purchase Decisions in Yogyakarta - Hartini Prasetyo Wulandari; Yoman Zending Nabutaek (Syntax Corporation Indonesia, 2023)
In this study, it was found that service quality and brand image both exert a positive and significant influence on the purchasing decisions of Mixue products in Yogyakarta. Furthermore, when analyzed together, service quality and brand image collectively hold a significant sway over Mixue purchasing decisions within the city. The research results align with prior studies in the field, emphasizing the importance of service quality as a dynamic factor that can meet or exceed customer expectations. Moreover, brand image plays a crucial role in consumer decision-making, as it reflects the associations and perceptions consumers have about a particular brand. The consistency of these findings across various studies underscores their relevance and applicability in real-world marketing scenarios. These insights are valuable for businesses, especially those in the culinary industry, as they highlight the significance of offering high-quality service and building a strong brand image to attract and retain customers. Understanding the interplay between service quality, brand image, and purchasing decisions can aid businesses in developing effective marketing strategies to thrive in a competitive marketplace. In conclusion, this research contributes to the body of knowledge in marketing management and provides practical guidance for businesses aiming to navigate the ever-changing landscape of consumer behavior. By adapting to these insights, companies can position themselves strategically to succeed in the market and win the competition.